Association of miR-223-3p and miR-223-5p gene expression with Levels of IgE, Vitamin D and Mg+2 in pediatric Asthma patients : miR-223-3p and miR-223-5p gene expression with Levels of IgE, Vitamin D and Mg+2 in pediatric Asthma patients - F. Al-Mashhadani, Duaa; Q. Alsaadi, Basima (Journal of Medical Biochemistry, 2025)
Background: Asthma, a global non-communicable disease, significantly impacts public health. Severe cases cause high morbidity and mortality rates, with childhood asthma rates in Iraq reaching 20%. The study investigated the expression levels of miR-223-3p and miR-223-5p genes linked to pediatric asthma and the impact of IgE, Vitamin D, and Mg+2 on asthma severity. Methods: A study of 140 children aged 1-10 years with allergic asthma was conducted in Baghdad from November 2023 to February 2024. The patients were divided into three groups: those under 1, those aged 1-5, and those over 5. Serum IgE, Vit D3, and Mg+2 levels were determined using the Immunoglobulin E Test Kit. Results: The results indicated a significant increase in the level of IgE in patients (353.812 ± 25.679 ng/ml) compared to the control group (25.320 ± 2.581 ng/ml) (p-value < 0.01, the serum level of Vit-D revealed a significant decrease in the patient group (16.907 ± 0.512 ng/mL) while in the control group, levels reached (32.746 ± 1.629 ng/mL), Mg⁺² serum level decreased in patient groups (2.168 ± 0.030 ng/dL) compared to control group (2.316 ± 0.028 ng/dL) at p-value < 0.01. also, this study shows that upregulation of gene expression in miR-223-3p and miR-223-5p genes are considered risk factors for allergic asthma. Conclusion: The study found that asthma patients had high IgE levels, low vitamin D3 and magnesium levels, and high gene expression in miR-223-3p and miR-223-5p genes, risk factors for allergic asthma.